2022
DOI: 10.1186/s40623-022-01723-1
|View full text |Cite
|
Sign up to set email alerts
|

Deep low-frequency earthquake activity associated with the 2018 eruptions in the Kirishima volcanic complex, Japan

Abstract: Deep low-frequency (DLF) earthquakes have occurred at depths of 10–30 km in the Kirishima volcanic complex, Japan. Here, we investigate the DLF earthquake activity that was associated with the 2018 eruptions, compare these DLF earthquakes with those associated with the 2011 eruptions, and provide inferences on magmatic fluid ascension during these two eruptions. We apply a new matched-filter method to the continuous waveform data from the 2017–2018 period to comprehensively detect the DLF earthquake activity s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Seismic interferometry revealed a slight decrease in seismic velocity beneath the crater in less than a month before the 2011 eruption, but no decrease before the 2018 eruption 43 . Kurihara et al 44 , 45 found that the event rate of deep low-frequency (DLF) earthquakes deeper than 17 km in the southeast (see star in Fig. 1 a) showed a good correlation with the deep inflation in the northwest prior to the eruptions.…”
Section: Introductionmentioning
confidence: 92%
“…Seismic interferometry revealed a slight decrease in seismic velocity beneath the crater in less than a month before the 2011 eruption, but no decrease before the 2018 eruption 43 . Kurihara et al 44 , 45 found that the event rate of deep low-frequency (DLF) earthquakes deeper than 17 km in the southeast (see star in Fig. 1 a) showed a good correlation with the deep inflation in the northwest prior to the eruptions.…”
Section: Introductionmentioning
confidence: 92%